Esophageal foreign body retrieved by cervical esophagotomy four years after ingestion - Felix Oyania; Robert Mugarura; Charles Newton odongo; Sarah Jane Commander; Martin Situma (Elsevier, 2023)
Background: Foreign body ingestion is common pediatric population with more than 55% from ingestion of coins. Over 80% pass spontaneously through the digestive tract, but substantial amount lodge in the UES causing esophageal perforation. Failure to recognize and treat as an emergency can cause significant complications and mortality aggravated by longer duration of impaction. Impacted FB can be retrieved by endoscopy with over 95% success rate. In the event of failed endoscopic retrieval, surgery offers safe alternative. The latter usually indicated in perforation, stricture, esophago-aortic and trachea-esophageal fistulas. Clinical case: A 12-year old female patient with a coin impaction in the cervical esophagus for over four years managed for recurrent respiratory infection. Conclusion: Foreign body - coins ingestion is common in pediatric population. Timely recognition and treatment is required to prevent severe complications and mortality. Diagnosis involves a triad of clinical history, X-ray appearances and esophagoscopy.